ELCONAS Electronic Control Using Android System With Bluetooth Communication And Sms Gateway Based Microcontroller - Ahmad Fadhil; Yandi Prasetia; Adiansyah Adiansyah; Titin Wahdania Tunnisa; Ayu Ambarwati; rossi Passarella (ICON-CSE, 2014)
ELCONAS (Electronic Control with Android System) is a tool designed to control electronic devices. This control Android via Bluetooth communication and SMS Gateway that can be controlled by the user. Control using Bluetooth, applied for a certain distance which is connected to android, Bluetooth with limited distance range of services and the use of the remote system is used SMS Gateway is connected via a short message that is sent to the microcontroller through a module that has been installed on the microcontroller, using ArdunioMega 2560. ELCONAS designed to minimize the occurrence of short circuits and even prevent fires because the user can handle it via the application without having to interact directly with electronic devices that are at home or office.